Nutrient Level Change Based on Calcareous Nannofossil Assemblages During Late Miocene in Banyumas Subbasin - Hendrizan, Marfasran (Geological Agency, 2016)
DOI:10.17014/ijog.3.3.183-194Hydrographic situation on surface waters is more challenging to be understood, related to global and regional climate change in tropical regions. In addition, records from these tropical areas are limited compared to other areas of subtropical and polar regions. The aim of this study is to reconstruct Cenozoic paleoceanography, in particular nutrient level, using outcrop samples from Kali Pasir, Banyumas, Indonesia. This study is focused on the relationships of the relative abundance of Discoaster, coccolith size of Reticulofenestra, and lithofacies characteristics. Nutrient level is reconstructed using quantitative analysis of calcareous nannofossil by counting calcareous nannofossils on 400 fields of View (FOV) for each sample. The abundance of Discoaster and the large Reticulofenestra represent a deep thermocline and nutricline, which is a typical of oligotrophic condition. This condition also associated with the muddy facies in the early stages of Late Miocene (NN8-NN10a). Conversely, decreasing Discoaster abundance and the abundance of small Reticulofenestra indicate a shallow thermocline and nutricline, resulting strong eutrophication of surface waters in the later stage of Late Miocene (NN10b-NN11). A high nutrient content in this stage is related to classical turbidite deposits. A change in a sea surface resulted in strong eutrophication, which is in this section similar to the eastern Indian Ocean micropaleontology records during the Late Miocene (NN10). This finding shows that strong eutrophication in Kali Pasir section is probably driven by nutrient-rich terrestrial material related to the onset of Indian monsoon during the Late Miocene.